Reactivation of latent hepatitis B infection during immunosuppressive therapy with guselkumab for plaque psoriasis: a case report - Elena Franchi; Arianna A. C. Costanzo; Carmela Cursaro; Amedeo Lonardo; Claudia Lasagni; Pietro Andreone (Exploration of Drug Science)
Reactivation of hepatitis B virus (HBV; RHBV) is a significant concern during immunosuppressive therapy, as it can lead to severe hepatitis and liver failure. The article reports a case of RHBV during treatment with guselkumab, an interleukin-23 inhibitor in a patient with inactive HBV infection and psoriasis. This report highlights the importance of screening for HBV prior to immunosuppressive therapy and initiating prophylactic therapy when necessary to prevent reactivation and its complications.